Genetic Diversity and the Spatio-Temporal Analyses of Hantaviruses in Shandong Province, China - Zuo, Shu-Qing; Li, Xiu-Jun; Wang, Zhi-Qiang; Jiang, Jia-Fu; Fang, Li-Qun; Zhang, Wen-Hui; Zhang, Jiu-Song; Zhao, Qiu-Min; Cao, Wu-Chun (Frontiers in Microbiology, 2018)
Hemorrhagic fever with renal syndrome (HFRS) is a serious public health problem in Shandong Province, China. We conducted an epizootiologic investigation and phylogeographic and phylodynamic analyses to infer the phylogenetic relationships of hantaviruses in space and time, and gain further insights into their evolutionary dynamics in Shandong Province. Our data indicated that the Seoul virus (SEOV) is distributed throughout Shandong, whereas Hantaan virus (HTNV) co-circulates with SEOV in the eastern and southern areas of Shandong. Their distribution showed strong geographic clustering. In addition, our analyses indicated multiple evolutionary paths, long-distance transmission, and demographic expansion events for SEOV in some areas. Selection pressure analyses revealed that negative selection on hantaviruses acted as the principal evolutionary force, whereas a little evidence of positive selection exists. We found that several positively selected sites were located within major functional regions and indicated the importance of these residues for adaptive evolution of hantaviruses.